1971
DOI: 10.3109/00016347109155078
|View full text |Cite
|
Sign up to set email alerts
|

IV Correlations of menstrual traits between adolescent girls and their mothers

Abstract: It has been claimed that daughters mimic the menstrual patterns of their mothers. For the present report the menstrual patterns of c. 5,000 menstruating girls and their mothers were studied. Comparisons were made under the following headings: constitution, age of menarche, cycle, duration, regularity of menstruation, premenstrual tension, and dysmenorrhoea. The correlations between the patterns of menstruation of mothers and daughters were highly significant. The highest correlation coefficients were found for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our results demonstrated that the prevalence of dysmenorrhea was dependent on family income. Similarly, Widholm and Kantero noted a higher prevalence of dysmenorrhea among higher income groups (45). However, some researchers have indicated that economic status is not consistently associated with dysmenorrhea, suggesting that further research is necessary to clarify this factor (46).…”
Section: Discussionmentioning
confidence: 97%
“…Our results demonstrated that the prevalence of dysmenorrhea was dependent on family income. Similarly, Widholm and Kantero noted a higher prevalence of dysmenorrhea among higher income groups (45). However, some researchers have indicated that economic status is not consistently associated with dysmenorrhea, suggesting that further research is necessary to clarify this factor (46).…”
Section: Discussionmentioning
confidence: 97%
“…Several early studies suggested genetic influences on premenstrual symptoms (Kantero & Widholm, 1971 ;Halbreich et al 1982 a, b). Methodological problems such as small samples (Dalton et al 1987), case reports (Taghavi, 1990), and inability to disentangle genetic and environmental influences (Futterman et al 1992) have been common.…”
Section: Introductionmentioning
confidence: 97%
“…Genetic influences have been identified on menstrual characteristics (Kantero n& Widholm, 1971 ;van den Akker et al 1987 ;Silberg et al 1987 ;Kendler et al a, 1998van den Akker et al 1995 ;Treloar et al 1998). Several early studies suggested genetic influences on premenstrual symptoms (Kantero & Widholm, 1971 ;Halbreich et al 1982 a, b). Methodological problems such as small samples (Dalton et al 1987), case reports (Taghavi, 1990), and inability to disentangle genetic and environmental influences (Futterman et al 1992) have been common.…”
Section: Introductionmentioning
confidence: 99%
“…This predisposition may be heritable, but the resulting phenotypic differences may have little bearing on an individual's fitness. The age at menarche appears to be heritable, with genetic variation accounting for 10-15% of the phenotypic variance, and the correlation between mothers' and daughters' menarcheal ages is typically around r = .30 (Damon et al 1969;Johnston 1974;Kantero and Widholm 1971;Surbey 1990). Whether variation in menarcheal timing is adaptive or not, a heritability greater than zero will result in behavior-genetic effects with both developmental rate and correlated behavioral characteristics transmitted between generations.…”
Section: Explanations For Intraspecific Variation In Life History Traitsmentioning
confidence: 99%